Post-treatment recovery of suboptimal DNA repair capacity and gene expression levels in colorectal cancer patients - Slyskova, Jana; Cordero, Francesca; Pardini, Barbara; Korenkova, Vlasta; Vymetalkova, Veronika; Bielik, Ludovit; Vodickova, Ludmila; Pitule, Pavel; Liska, Vaclav; Matejka, Vit Martin; Levy, Miroslav; Buchler, Tomas; et al. (Molecular carcinogenesis, 2015)
DNA repair in blood cells was observed to be suboptimal in cancer patients at diagnosis, including colorectal cancer (CRC). To explore the causality of this phenomenon, we studied the dynamics of DNA repair from diagnosis to 1 yr follow-up, and with respect to CRC treatment. Systemic CRC therapy is targeted to DNA damage induction and DNA repair is thus of interest. CRC patients were blood-sampled three times in 6-mo intervals, starting at the diagnosis, and compared to healthy controls. DNA repair was characterized by mRNA levels of 40 repair genes, by capacity of nucleotide excision repair (NER), and by levels of DNA strand breaks (SBs). NER and base excision repair genes were significantly under-expressed (P < 0.016) in patients at diagnosis compared to controls, in accordance with reduced NER function (P = 0.008) and increased SBs (P = 0.015). Six months later, there was an increase of NER capacity, but not of gene expression levels, in treated patients only. A year from diagnosis, gene expression profiles and NER capacity were significantly modified in all patients and were no longer different from those measured in controls. All patients were free of relapse at the last sampling, so we were unable to clarify the impact of DNA repair parameters on treatment response. However, we identified a panel of blood DNA repair-related markers discerning acute stage of the disease from the remission period. In conclusion, our results support a model in which DNA repair is altered as a result of cancer.
Keywords: DNA Breaks; Gene Expression Regulation, Neoplastic; kolon; follow-up study; Male; kolorektální nádory; Rectum; protinádorové látky; zlomy DNA; následné studie; biomarker; regulace genové exprese u nádorů; DNA repair; Aged; Case-Control Studies; mužské pohlaví; senioři; rektum; Follow-Up Studies; DNA Repair; Colorectal cancer; oprava DNA; anti-cancer therapy; lidé; ženské pohlaví; studie případů a kontrol; Humans; Colon; Colorectal Neoplasms; DNA instability; Female; lidé středního věku; Antineoplastic Agents; Middle Aged